2011
DOI: 10.1038/gt.2011.118
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging gene delivery in a mouse model of congenital neuronal ceroid lipofuscinosis

Abstract: Adeno-associated virus (AAV) mediated gene replacement for lysosomal disorders have been spurred by the ability of some serotypes to efficiently transduce neurons in the brain and by the ability of lysosomal enzymes to cross-correct among cells. Here, we explored enzyme replacement therapy in a knock-out mouse model of congenital neuronal ceroid lipofuscinosis (NCL), the most severe of the NCLs in humans. The missing protease in this disorder, cathepsin D (CathD) has high levels in the central nervous system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Quality of life improved profoundly, with only 2 of 12 treated animals having progressed to the most debilitating symptoms such as dysequilibrium and severe ataxia. Clinical outcomes were similar for the 2 vector serotypes tested: AAV1, currently in human clinical trials (3639) or approved for human use (40, 41), and AAVrh8, a new serotype (42) that showed promise in a related feline model (28). …”
Section: Discussionmentioning
confidence: 93%
“…Quality of life improved profoundly, with only 2 of 12 treated animals having progressed to the most debilitating symptoms such as dysequilibrium and severe ataxia. Clinical outcomes were similar for the 2 vector serotypes tested: AAV1, currently in human clinical trials (3639) or approved for human use (40, 41), and AAVrh8, a new serotype (42) that showed promise in a related feline model (28). …”
Section: Discussionmentioning
confidence: 93%
“…The rapidly expanding body of research into normal glial biology and their responses to disease has facilitated a reassessment that glia are not just passive bystanders of pathology in the CNS, but instead are active determinants of neurodegeneration. As summarized in this review, there is substantial evidence suggesting such glial involvement in NCL pathophysiology, and changes in glial activation are frequently used to evaluate therapeutic efficacy in preclinical studies ( 4 , 11 , 15 , 23 , 26 , 34 , 43 47 , 97 ). Of necessity, this review focusses primarily upon the three most common forms of NCL, CLN1 disease, CLN2 disease and CLN3 disease, in which the issue of glial contribution to pathogenesis has been considered.…”
Section: Discussionmentioning
confidence: 99%
“…This approach theoretically has the advantage that a single one-time administration of viral vector should restore deficient lysosomal proteins to transduced cells ( 41 , 42 ). Preclinical studies of gene therapy in animal models of CLN1, CLN2, CLN3, CLN6, CLN7, and CLN10 diseases have shown promising results ( 4 , 23 , 34 , 43 47 ). However, clinical studies in children with CLN2 disease treated with gene therapy showed considerably less efficacy ( 48 , 49 ), highlighting the difficulty of translating advances from mice directly into human patients ( 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the significant attenuation of disease progression has also been observed in a recent clinical trial on CLN2 patients treated biweekly with intracerebroventricular injections of recombinant TPP1 [ 103 ]. Remarkable therapeutic outcomes have also been achieved in the Ctsd ko mouse, despite the rapid disease progression using an adeno-associated virus (AAV) vector-mediated gene transfer to the brain and/or the viscera [ 52 , 104 ]. Furthermore, we recently showed that injections of recombinant human pro-CTSD (rhCTSD) resulted in the partial correction of various pathological markers in the brain, the attenuation of the visceral pathology and a prolonged life span of treated mice [ 53 ].…”
Section: Discussionmentioning
confidence: 99%